Information retrieval in Social Defense Event Records in the State of Minas Gerais: a public security intelligence analysis - Farias, Renato Sena; Pires Moreira, Renato; Silva, Patrícia Nascimento; Peixoto Bax, Marcello (Ciência da Informação em Revista, 2024)
The Registration of Social Defense Events is a system used by security organizations in the state of Minas Gerais to record incidents, initiate investigations, and report other activities related to civil defense, enabling the performance of police intelligence analysis. Police intelligence analysis plays a fundamental role in crime prevention and combat. It involves the collection, organization, analysis, and interpretation of data to obtain information and produce knowledge that assists in making strategic decisions at all levels. In this context, this article seeks to identify the entry and indexing of data and information in the Registration of Social Defense Events and propose solutions for more efficient information retrieval in order to optimize intelligence analysis. The method used was the hypothetical-deductive approach, given the perceived gap in the topic at hand. The study identified that the use of generic terms and incorrect field entries in the Registration of Social Defense Events are complicating factors, compromising analyses, and hindering information retrieval. These points should be considered as potential solutions for more efficient information retrieval.